Implementation of One Stop Service at the Yogyakarta City Licensing Service in Improving the Investment Climate in the City of Yogyakarta in 2020 - Said Hamzali (MultiTech Publisher, 2023)
This study aims to find out: 1) the implementation of OSS at the Yogyakarta City Licensing Service in improving the investment climate in 2020, 2) the factors that influence improving the investment climate in 2020. This research uses a qualitative descriptive method to describe the implementation of OSS at the Yogyakarta City Licensing Service in improving the investment climate in 2020. Based on the research results, the implementation of OSS at the Yogyakarta City Licensing Service in improving the investment climate in 2020, studied with the theory of public service quality shows that the quality of service is very good (A) with an average index value of 3.26. Based on the results of this study, it can be concluded that the implementation of OSS at the Yogyakarta City Licensing Service in improving the investment climate has been very good because the investment licensing process is transparent, has time and cost certainty so that potential investors are interested in investing in Yogyakarta City which will have an impact on growth of economy in the city of Yogyakarta.